Circulating microRNA‐133, microRNA‐17 and microRNA‐25 in serum and its potential diagnostic value in gastric cancer. Issue 8 (12th March 2019) - ZiaSarabi, Parisa; Sorayayi, Saba; Hesari, AmirReza; Ghasemi, Faezeh
Abstract: Gastric cancer is one of the most common malignancies in the world and is considered as the most lethal gastrointestinal cancer. microRNAs (miRNAs) can be very important in detecting a disease at an early stage. The aim of this study was to investigate the microRNA‐17 (miR‐17), miR‐25, and miR‐133b in the serum of gastric cancer subjects. Serum samples were obtained from 120 gastric cancers and 102 healthy subjects. We evaluated expression levels of miR‐17, miR‐25 and miR‐133b by quantitative real‐time polymerase chain reaction. Our results showed that in the patients with gastric cancer, the expression level of miR‐17 and miR‐25 were significantly increased compared with the control group ( P < 0.5), while the expression level of miR‐133b was significantly decreased in patient groups compared with control cases ( P < 0.5). It seems that expression of miRNAs in Iranian patients with gastric cancer is similar to other patients in other populations. These findings suggested that miR‐17, miR‐25 and miR‐133b could be introduced as potential diagnostic candidates for the detection in gastric cancer patients in the early stage.